The diversity of malignant rhabdoid tumours : a morphological, immunohistochemical and ultrastructural review of cases from the Red Cross Children's Hospital and Groote Schuur Hospitals - Mostert, Colin (Division of Anatomical Pathology, 2018)
Malignant rhabdoid tumours of the kidney are rare childhood neoplasms. Extra-renal rhabdoid tumours are known to have a distinctive biological behaviour and do not always occur in the paediatric age group. As the histogenesis of rhabdoid tumours, and their apparent relationship to nephroblastoma is still unclear, careful assessment of new cases is required. This investigation illustrates diverse ultrastructural, light microscopic and immunohistochemical findings. These features are related to each other and to the biological behaviour of renal rhabdoid tumours, and six extra-renal lesions with rhabdoid features obtained from the Pathology Archives of the Red Cross Children's Hospital and Groote Schuur Hospital. In this series primitive epithelial elements are a dominant feature, but ultrastructural features of one renal rumour suggest diverse differentiation. The extra-renal lesions investigated include three undifferentiated rhabdoid lesions, a primitive neuro-ectodermal tumour, a malignant epithelioid Schwannoma and a possible undifferentiated hepatocellular carcinoma; all showing areas of extensive rhabdoid differentiation. Pseudo-rhabdoid cells in an additional two cases were also examined. These particular tumours were a nephroblastoma and a fibro-lamellar carcinoma of the liver. These rhabdoid tumour mimics were ultrastructurally different from true rhabdoid cells. Strong immunohistochemical co-expression of Vimentin and cytokeratin in rhabdoid tumour cell inclusions has been noted by previous investigators. (Vogel, 1984) (Gansler, 1991), (Berry, 1992). We speculate that the predominant line of differentiation in renal rhabdoid tumours is epithelial although, as in nephroblastoma multiple lines of differentiation may occur. The extra-renal lesions appear to represent more than one entity, but once again epithelial or neuro-epithelial differentiation appears to be present. Ultrastructural examination is a more useful investigation than immunohistochemistry because of inherent non-specific uptake of antibodies by the filamentous cytoplasmic inclusions.